Sobre la danza con crótalos en el egipto tardoantiguo (Mantichora. Italian Journal of Performance Studies, 2021)
In the artistic productions of late-ancient Egypt, the figure of the crotalistriadancer appears linked to the Dionysian environment, although it has iconographic features that relate her to Artemis and Aphrodite. Its image evokes, according to the most widespread interpretation, an archaic ritual of oriental origin that would have endured as a professionalized erotic show in the Roman and late-ancient world. In her late formal evolution, the crotalistria dancer appears naked and isolated from the religious cortege, in addition, she tends towards a schematic form that multiplies in objects and fabrics of a domestic nature where she supposedly acquires an apotropaic function. Two lines of inquiry emerge after characterizing the image: the process of defining a formal scheme and its significance in the late-ancient social and religious context, both closely related issues. The hypothesis thatarises is that the dancer act out as an evocation of the young nubile at the gates of marriage.